2020
DOI: 10.1177/1096348020957075
|View full text |Cite
|
Sign up to set email alerts
|

More is Not Better: The Emotional Dynamics of an Excellent Experience

Abstract: Emotions embody the value in tourism experiences and drive essential outcomes such as intent to recommend. Current models do not explain how the ebb and flow of emotional arousal during an experience relate to outcomes, however. We analyzed 15 participants’ experiences at the Vincentre museum and guided village tour in Nuenen, the Netherlands. This Vincent van Gogh-themed experience led to a wide range of intent to recommend and emotional arousal, measured as continuous phasic skin conductance, across particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
(66 reference statements)
0
13
1
1
Order By: Relevance
“… Li (2021) indicated that if tourists have PE, these remarkable experiences will further influence their recommended intentions. Mitas et al (2020) also found that participants who are highly recommended because their emotions arouse a peak during tourism, this peak is higher than the emotion level before and after the tourism. This raises an interesting question that will employees’ WOM referrals be influenced if they have PE?…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… Li (2021) indicated that if tourists have PE, these remarkable experiences will further influence their recommended intentions. Mitas et al (2020) also found that participants who are highly recommended because their emotions arouse a peak during tourism, this peak is higher than the emotion level before and after the tourism. This raises an interesting question that will employees’ WOM referrals be influenced if they have PE?…”
Section: Discussionmentioning
confidence: 90%
“…Research on tourism experiences has proven that companionship plays a key role in shaping memorable tourism experiences ( Vada et al, 2022 ). This episode is remembered mostly because it exceeded a certain level of emotional arousal ( Mitas et al, 2020 ). Thus, we can infer that companionship is essential for EPE, which is a highly positive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…In the tourism experience, emotions embody the value, mediate recommendation and other behavioural outcomes, and fuel social meanings. Emotions also give practitioners the best entry point for measuring and managing experiences (Mitas et al, 2020). Emotions are crucial in determining whether tourist experiences are actually remembered, which is a prerequisite for experiences to take on long-term meaning (Bastiaansen et al, 2019).…”
Section: Connecting: Engaging Peoplementioning
confidence: 99%
“…Actively participating in the committee hearing despite the lengthy procedure. Emotions embody the value in tourism experiences and drive essential outcomes such as intent to recommend (Mitas, 2022). In the context of the cultural workers, primarily proposing the establishment of the Kagikan museum drove them into excitement.…”
Section: Excitement In Planning the Kagikan Museummentioning
confidence: 99%